Koszty wprowadzenia waluty euro w przedsiębiorstwach niemieckich (analiza wyników ankiety) - Knieper, Anna (Costs of Introducing of the Euro in German Companies (Review of the Survey Results), 2008)
The subject of the article concerns findings from a survey of the technical and organizational costs incurred by German companies with regard to their readjustment to the euro. The survey sets out to examine the costs of adjustment o the euro by German companies, the range of amounts and how they were formulated in company balance records. The article presents conclusions of the research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (6); 2008; nr 1196, s. 67-81